ANALYSIS OF NURSING STUDENTS NEEDS FOR CHILD DEVELOPMENT SCREENING LEARNING THROUGH CASE-BASED VIRTUAL SIMUALTION - Nur Eni Lestari; Hari Ghanesia Istiani; Oscar Fidel Antunez Martinez; Mohammad Fathul Qorib (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Introduction: Nursing education requires innovative approaches to overcome limitations in clinical practice, particularly in child development screening. Case-based virtual simulation has become a promising alternative for enhancing nursing students' skills in handling real clinical situations.Methods: This study aims to analyze the needs of nursing students regarding child development screening learning using case-based virtual simulation. The research method used was descriptive quantitative research, with data collected through questionnaires distributed to 84 nursing students. The questionnaire covered five leading indicators: the availability and limitations of clinical practice, difficulties in understanding child development concepts, the need for digital learning media, preferences for interactive and case-based media, and responses to the use of technology in learning.Results: The results showed that students experienced limitations in gaining direct practical experience in field-based child development screening (average scores 3.5–3.7) and in understanding child development concepts without illustrations or real case examples (average score 3.5). Students also expressed a strong need for flexible, interactive digital learning media (average score: 3.9). Moreover, students preferred case-based learning that supports clinical decision-making (average score: 3.6).Conclusion: The study concluded that the development of case-based virtual simulations can overcome the limitations of clinical practice and provide a more applicable learning experience. Technology-based learning media can be integrated into nursing education to improve students' clinical preparedness in conducting child development screening.